Fare e disfare territori. Percorsi urbani e futuri alternativi negli usi di sostanze - Nistri, Giulia (Antropologia Pubblica, 2024)
This paper, based on my PhD research, reflects on different ways of crossing areas and spaces of life to explore possibilities of urban and existential transformations. Ethnography, drawing connections between places and people, was carried out involving consumers and users of substances and workers of health and outreach Services. Walking through the city with informants helps to perceive organizations and textures of spaces, feeling also rhythms that tend to circumscribe territories and regulate forms of lives. Lives that, sometimes, flowing, can trace trajectories capable of blurring boundaries and fences, creatively subverting entrances and exits. Recalling surrealistic aesthetics and practices of montage, the article tries to explore the ways different movements and heterogeneous assemblages and productions, make and unmake territories. Following the intertwining of urban and existential trajectories, the text aims to trace a cartography moving through the potentialities of transformation and connections of the intensive and extensive experiences that take shape in the daily lives of the people I walked with. Experiences of movements, stories, and experiments that turn central for an ethnography that try to grasp ways and possibilities of carving out niches of life, sometimes amidst suffering and impasse, and picking up hints, sometimes residual, of the realization of alternative futures.